Do elite scientists play a key role in the genesis of transformative research of “sparking type”? An investigation in the science of science - Xi, Fangjie; Rousseau, Ronald; Hu, Xiaojun (Malaysian Journal of Library and Information Science, 2022)
The purpose of this study is to explore if elite scientists play a key role in the genesis of transformative research. As there exist different types of transformative research, this paper focuses on one type of work, i.e. under-cited influential work,referred to as “sparking” articles. A comparative study between the h-indices of authors citing Nobel Prize-winning papers of sparking type and those of authors citing ordinary ones is conducted, focusing on the first author and the corresponding author of each paper. The results show that the citers of the Top 1% or Top 10% Citations Sets in the sparking group have much higher h-indices than those in the ordinary group. These findings imply that elite scientists, operationalized as those with a high h-index in the corresponding fields, are more sensitive to sparking work and, as such play a pivotal role in the genesis of transformative research. This investigation provides new insight into the study of detecting transformative research, and hence, contributes to the science of science.